Nitric Oxide, Procalcitonin and Oxidative Stress Index Levels in Acute Bronchitis Patients - Abdulsada, Huda A.; Taha, Ekhlass M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Acute bronchitis, an inflammation of the lower respiratory tract characterized by an acute cough, is a prevalent clinical illness that leads patients to seek out primary healthcare services. About 5 percent of adults in the United States report having acute bronchitis annually, with 90 percent of those affected seeking medical attention.Objectives: The study aimed to determine Nitric oxide, Procalcitonin (PCT), WBCs, neutrophils, lymphocytes, and Oxidative stress index (OSI) levels in acute bronchitis patients.Methods: The study involved 120 volunteers aged 20–50 years old in Al-Zahra Teaching Hospital, Wasit City. 80 patients with acute bronchitis were conducted between (10 November 2022 to 20 March 2023). 40 people were used as a control group. Blood samples were collected from patients and controls. Complete blood account CBC was calculated using a blood sample with EDTA. Serum was used to calculate NO, PCT, and OSI. Blood counts were performed using the SYSMEX XP-300. Nitric oxide and Procalcitonin levels were measured using an ELISA kit. OSI was calculated using the equation OSI = Total oxidant status /Total antioxidant status x100.Results: The current research presents the results of the Procalcitonin, nitric oxide, oxidative stress index, neutrophils, and lymphocytes. Age, BMI, and WBCs in acute bronchitis did not show any significant variances when compared between the two groups. In contrast, nitric oxide, Procalcitonin, oxidative stress, and Neutrophil levels showed a highly significant change among the acute bronchitis patient group compared to the control group.Conclusion: Procalcitonin and nitric oxide may have a role in the diagnosis of acute bronchitis, in addition to lymphocytes and neutrophils.